Ragnarok - Christensen, Henrik Bærbak (DAIMI Report Series, 1996)
This report describes the current state of my research in software development environments. I argue in favour of strong support for project management, comprehension and navigation, and collaboration primarily based on experiences from developing large-scale industrial-strength applications. An underlying model of such an environment, named ``Ragnarok´´, is outlined. A design and first prototype of important parts of Ragnarok is described as well as some results from initial experiments.